Prevalence and factors associated with mild cognitive impairment among older Malaysians - Kamarolzaman, Khairiah (2015)
Despite mortality due to communicable diseases, dementia incidence is destined to increase in the developing world in tandem with the ageing population. In Malaysia, one of the significant health problems among elderly is Dementia. Studies show that mild cognitive impairment elderly tend to have lower compliance to medication and they are at higher risk of developing dementia later on. However, a little study was done in this field in Malaysia. Recognizing the importance of finding the factors associated with the occurrences of the early stage of dementia, this study focussed on describing nationwide study of mild cognitive impairment prevalence and its socio-demographic risk factors and health correlates among older Malaysians. This is community centred cross-sectional study conducted among elderly aged 60 and above in four states of Malaysia - Perak, Kelantan, Selangor and Johor. A Multi-stage stratified random sampling method was used for the data collection. The study was conducted from May 2012 to April 2014. A structured questionnaire was used to conduct the study through a face to face interview to obtained socio-demographic data. Mini Mental State Examination ≤22 was used to diagnosed mild cognitive impairment. A multivariate logistic regression was used to do the analysis. Ethics approval was obtained from National Medical Research Register prior to the study. A total of 2112 older patients were entered into the analysis. The mean age of the patients was 69.2 years and 51.4% were female. The ethnics distribution was 63.4% Malay, 31.4% Chinese, 5% Indians and 0.2% other ethnic. The overall prevalence of mild cognitive impairment was 68% (N=1436/2112). In multivariate logistic regression analysis, respondents with older age (odds ratio OR 1.02, 95% confidence interval [CI] 1.00-1.04) were more likely to have mild cognitive impairment compared to that younger age. Similarly, those with no formal education (OR 6.85, 95% CI 4.58-10.25), primary education (OR 2.35 95% CI 1.84-3.00), loneliness (OR 1.18 95% CI 1.05-1.32) and low level of life satisfaction (OR 1.68 95% CI 1.02-2.67) were more likely to be associated with mild cognitive impairment in this population. Mild cognitive impairment is present in one in two elderly Malaysian. Aging population, presence of low education level, loneliness and dissatisfaction towards life were more likely to develop mild cognitive impairment.